1999
DOI: 10.1103/physrevc.60.065502
|View full text |Cite
|
Sign up to set email alerts
|

Superscaling of inclusive electron scattering from nuclei

Abstract: We investigate the degree to which the concept of superscaling, initially developed within the framework of the relativistic Fermi gas model, applies to inclusive electron scattering from nuclei. We find that data obtained from the low energy loss side of the quasielastic peak exhibit the superscaling property, i.e. the scaling functions f (ψ ′ ) are not only independent of momentum transfer (the usual type of scaling: scaling of the first kind), but coincide for A ≥ 4 when plotted versus a dimensionless scali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
418
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(442 citation statements)
references
References 56 publications
24
418
0
Order By: Relevance
“…On the contrary, the transverse contribution f T (ψ ) overestimates the data by ∼ 20% even in the region close to the maximum, ψ ≈ 0. This result, arising from zeroth-kind scaling violation in the RMF approach, is not in conflict with (e, e ) data that indeed leaves room for effects of this type (see the general discussion in [3,4]). …”
mentioning
confidence: 77%
See 2 more Smart Citations
“…On the contrary, the transverse contribution f T (ψ ) overestimates the data by ∼ 20% even in the region close to the maximum, ψ ≈ 0. This result, arising from zeroth-kind scaling violation in the RMF approach, is not in conflict with (e, e ) data that indeed leaves room for effects of this type (see the general discussion in [3,4]). …”
mentioning
confidence: 77%
“…The data analysis of the separated longitudinal (L) and transverse (T ) contributions to the scaling function carried out in [3,4] has shown that, whereas the L response does scale to a universal curve, the T strength increases with the transfer momentum q and/or the mass number A. This excess of strength in the transverse channel is not entirely understood, although different effects ranging from FSI effects to MEC contributions have been invoked to explain it.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…which scales in the region where the RFG is expected to be a reasonable model, specifically at q > 2p F where Pauli blocking effects are absent [4,5,6]. That is, it depends only upon a single variable ψ, whose square is given by…”
mentioning
confidence: 99%
“…The theoretical concept of superscaling has been introduced within the relativistic Fermi gas (RFG) model [21,22]. In the RFG model the scaling function f RFG (ψ ) = k F · F has the form [23]: As pointed out in [23], however, the actual dynamical physical reason of the superscaling is more complex than that provided by the RFG model. In Ref.…”
Section: Theoretical Scheme and Resultsmentioning
confidence: 99%